Wireless power transfer : theory, technology, and applications - Shinohara, Naoki, 1968- (IET energy engineering series, 2018)
The book has 13 chapter. Chapter 1 covers the introduction. Chapter 2 and 3 presents the basic theory of inductive coupling and resonance coupling WPT. Chapter 4 is intended for multihop wireless power transmission. Chapter 5 outlined the circuit theory on wireless couplers. Chapter 6 discussed the inverter/rectifier technologies on WPT systems. Chapter 7 and 8 covers the basic theory of wireless power transfer via radio waves. Chapter 8 is for technologies of antenna and phased array for wireless power transfer via radio waves. Chapter 9 outlined the transmitter/rectifier technologies in WPT via radio waves. Chapter 10 is for applications of coupling WPT for electric vehicle. Chapter 11 discussed the applications of long-distance wireless power transfer. Chapter 12 presents the biological issue of electromagnetic fields and waves and the last chapter discussed the impact of electromagnetic interference arising from wireless power transfer upon implantable medical device.